Distal intestinal obstruction syndrome as unusual manifestation of cystic fibrosis. Report of a case - Gómez Ruiz Alejandro; Santos Jasso Karla Alejandra; Asz Sigall José (Instituto Nacional de Pediatría, 2014)
Introduction: Distal intestinal obstruction syndrome (DIOS) or "meconium ileus equivalent" is a blockage of the terminal ileum or of the ascending colon caused by inspissated stools in patients with cystic fibrosis (CF) beyond the neonatal period. We report the case of a girl who presented with DIOS as an unusual manifestation which lead to the diagnosis of CF. Case presentation: A 7 year-old female presented with bowel ob- struction that required an exploratory laparotomy. Abundant inspis- sated stools were found obstructing the distal ileum. An enterotomy with extraction of the inspissated material was performed. A few days later the patient presented once more with acute abdomen requiring a second exploratory laparotomy. Dehiscence of the intestinal suture line was found and an ileostomy with mucous fistula was carried out. The histopathologic study showed findings compatible with CF and the sweat chloride test confirmed the diagnosis. Discussion: DIOS as the first manifestation of CF is very unusual. It is important to know this entity and to have a high index of suspicion to diagnose CF when it is found. If DIOS is suspected, conservative treatment should be tried before subjecting the patient to surgery.